THE ROLE OF MAKHARIJ AL-HURUF IN KEEPING THE MEANING OF THE QUR’AN VERSES - Hidayatul Azizah Gazali; Sefri Auliya (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2020)
Abstract: Many moslem people are not quite right and even wrong in reading verse of the Qur’an. Unconsciously, it can damage the meaning and interpretation. One reason is when the reader does not learn and understand in advance the science of how to read the Qur’an correctly and well, known as the science of Tajwid. Among the discussions of Tajwid which plays an important role in maintaining the meaning of the Qur’an verse is the science of Makharij al-Huruf. This science learns how to pronounce the letters of the Qur’an properly and correctly and in accordance with what was taught by the Prophet Muhammad. Mistakes in pronounciation can damage the meaning of the verse, but on the other hand there are also those that do not damage the meaning. For example, فَصَلِّ لِرَبِّكَ وَانْحَرْ read by فَصَلِّ لِرَبِّكَ وَانْهَر (the letter of ح read like the sound of ه), where errors in pronouncing the letter will change the original meaning.